PEMENUHAN AIR BERSIH METODA RAIN WATER HARVESTING SKALA RUMAH TINGGAL SEBAGAI SOLUSI TEKNOLOGI YANG EKOLOGIS (Meeting the Clean Water Sufficiency by Implementing Residential-Scaled Rain Water Harvesting Method as a Ecologically Technological Solution) - F. X. Bambang Suskiyatno (Tesa Arsitektur, 2013)
ABSTRAC.T Lack of clean water supply is one of the serious societal problems, especially in big cities in Indonesia. Water is usually got from groundwater and shallow groundwater resources. They having low income can only get surface water sources (rivers) that is very low qualified and to bring assorted illness. Actually there is another source spending abundant of clean water that can be utilized besides reducing the environmental destruction impacts. It is rain water. As it is known that rain, for the time being, tend to puddle and to lead to flooding, especially in downtowns. Rain also causes land- sliding because there is no open land remaining to absorb the rainwater. All ground surfaces are coated with a water-resistant pavement, including watelWays. Rain water utilization as clean water will minimize the possibility of these effects. Such rainwater utilization is known as Rain water Harvesting System for getting clean water. By having certain technologies rain water utilization can be easily done at a residential scale, both simple to advanced technologies. Keywords: clean water, environment, rain water. ABSTRAK Kurangnya pemenuhan kebutuhan air bersih bagi masyarakat merupakan persoalan yang cukup besar. Terutama di kota-kota besar di Indonesia. Sumber air bersih tersebut adalah dari air tanah dangkal maupun air tanah dangkal. Sementara bagi masyarakat dengan tingkat ekonomi rendah hanya dapat memanfaatkan sumber air permukaan (sungai) dengan kualitas sangat rendah dan berindikasi menyebabkan penyakit. Sebenarnya terdapat sumber air bersih lain yang tidak kurang dalam jumlah yang dapat dimanfaatkan dan justru dapat mengurangi dampak perusakan lingkungan adalah air hujan. Seperti diketahui bahwa pada masa sekarang, hujan lebih mengakibatkan genangangenangan air bahkan banjir di daerah bawah dan juga kelongsoran tanah, karena hampir tidak tersisanya tanah terbuka di derah perkotaan yang mampu menyerap air hujan. Semua permukaan tanah dilapis dengan perkerasan yang kedap air, termasuk juga saluran air. Pemanfaatan air hujan sebagai air bersih justru dapat meminimalisir kemungkinan dampakdampak tersebut. Bentuk dari pemanfaatan air hujan sebagai air bersih dikenal dengan Sistem Pemanenan Air Hujan (Rain Water Harvesting) untuk air bersih. Dengan teknologi tertentu pemanfaatan air hujan dapat dilakukan dengan mudah pada skala rumah tingga/ baik dengan teknologi yang sederhana sampai tinggi.